Measuring the Content Validity of MEPI using Content Validity Ratio - Norashady Mohd Noor; Muhammad Aziz Shah Mohamed Arip; Eftah Moh @ Hj Abdullah; Haniza Yon (Pejabat Karang Mengarang UPSI, 2019)
The main intention of this research is to examine the content validity of Marine Engineer Personality Inventory or MEPI for student candidates of Diploma in Marine Engineering course at Malaysian Polytechnics by using Content Validity Ratio (CVR). The assessment was conducted through the evaluation among 14 subject matter experts (SME) selected via judgment sampling. Seven professional university experts involved with the expertise in psychology, psychometric, educational measurement, and linguistics. The field experts specializing in particular fields of study consisted of seven practitioners who worked in the polytechnics field and maritime industry. The instrument involved 288 items with six main constructs. The results of the research show that the instrument has a good content validity and proved that MEPI has great potential to be promoted as a good measurement instrument of personality screening for Marine Engineering student selection process. It is recommended to apply more sophisticated statistical analysis, such as the Item Response Theory (IRT) model for elaborating on quality items.